1996
DOI: 10.1089/clm.1996.14.59
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy (PDT) and Photodiagnosis (PD) Using Endogenous Photosensitization Induced by 5-Aminolevulinic Acid (ALA): Current Clinical and Development Status

Abstract: Exogenous provision of 5-aminolevulinic acid (ALA) to many tissues results in the accumulation of sufficient quantities of the endogenous photosensitizer protoporphyrin IX (PpIX) via the heme biosynthetic pathway, to produce a photodynamic effect when exposed to activating light. Therefore, ALA may be considered the only current photodynamic therapy (PDT) agent in clinical development that is a biochemical precursor of a photosensitizer. Topical ALA application, followed by exposure to activating light (ALA PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 15 publications
0
37
0
1
Order By: Relevance
“…Exogenously administered ALA bypasses this control point and induces intracellular accumulation of PpIX (Kennedy and Pottier, 1992). Selectivity of PpIX accumulation in malignant and premalignant tissue has been demonstrated in a number of animal models and in human clinical studies, and may be useful for enhancing visual detection of tumors, including bladder malignancies (Marcus et al, 1996). ALA may also have a role in the treatment of esophageal cancer and squamous cell carcinoma (Ackroyd et al, 2000;Hinnen et al, 2000).…”
mentioning
confidence: 99%
“…Exogenously administered ALA bypasses this control point and induces intracellular accumulation of PpIX (Kennedy and Pottier, 1992). Selectivity of PpIX accumulation in malignant and premalignant tissue has been demonstrated in a number of animal models and in human clinical studies, and may be useful for enhancing visual detection of tumors, including bladder malignancies (Marcus et al, 1996). ALA may also have a role in the treatment of esophageal cancer and squamous cell carcinoma (Ackroyd et al, 2000;Hinnen et al, 2000).…”
mentioning
confidence: 99%
“…In some tumours, deaminase-isomerase, the rate-limiting enzyme that converts porphobilinogen into uroporphyrinogen in the haem synthesis pathway is increased and ferrochelatase is reduced, so that PPIX accumulates preferentially in tumour cells (Hua et al, 1995;Heyerdahl et al, 1997;Peng et al, 1997). Photosensitization by ALA-induced PPIX is tissue specific and is primarily enhanced in tissues that cover body surfaces, or line body cavities and exocrine glands such as mammary glands (Kennedy and Pottier, 1994;Marcus et al, 1996;Riesenberg et al, 1996).…”
mentioning
confidence: 99%
“…This is a rate-limiting precursor in heme biosynthesis such that, when given in excess, it leads to increased levels of the fluorescent photosensitizer protoporphyrin IX ͑PpIX͒. 35 Many studies in different organs, such as the bladder, cervix, and lung, have shown that ALA-PpIX can give high fluorescence contrast in early malignancy, 21,35 most likely due to increased metabolic rate and/or to reduced ferrochelatase, the enzyme responsible for converting PpIX to heme. ALA-PpIX has been studied extensively for photodynamic therapy for numerous early stage lesions, including dysplasia in BE, as discussed later.…”
Section: Methods To Improve White-light Endoscopymentioning
confidence: 99%